Pengaruh Bermain Plastisin Terhadap Perkembangan Kreativitas Anak Di TK Negeri Satap Desa Sibargot - Nursani Rambe; Soybatul Aslamiah Ritonga; Azhar (Jurnal Zeniusi, 2024)
Playing with playdough is a constructive play.  Creativity generates a new idea that connects with the previous one, creating something new.  The problem formulation in this research is "Is there an influence of using plasticine media on the development of early childhood creativity at TK Negeri Satap Desa Sibargot."  The research aims to determine the effect of plasticine media on developing creativity in early childhood at TK Negeri Satap Desa Sibargot. This research uses a quasi-experimental quantitative research design with a control class, where the experimental class consists of 15 children and the control class consists of 15 children. Data were collected using the observation guideline technique of the child creativity development research instrument.  The analysis technique uses data homogeneity, normality, and paired sample t test/hypothesis testing techniques. Hypothesis analysis is used to test the hypothesis using the t-test in the SPSS 17 program, namely, t-test = 15.453 sig 0.000.  Therefore, the sig (2-tailed) value of 0.520 > 0.000 means that H0 is rejected and H1 is accepted.  Thus, the research hypothesis stating that using colored flour playdough media affects the development of creativity in early childhood at TK Negeri Satap Desa Sibargot is accepted as true.